Perbandingan Sastra Dalam Puisi “Water Karya Koleka Putuma Dan Puisi Peringatan Karya Wiji Tukul” - Sylvia Friska Dara Citra; Erika Retnosari; Muhammad Rohman (Menulis: Jurnal Penelitian Nusantara, 2025)
This study aims to conduct a comparative literature on two poetic works that have the theme of resistance against oppression, namely the poem "Water" by Koleka Putuma (South Africa) and the poem "Warning" by Wiji Thukul (Indonesia). Through qualitative research methods with content analysis techniques, this study examines the differences and similarities in intrinsic elements, especially the theme, style of language (figures of speech), diction, and the message of both poems. The results of the comparison show that although both have the theme of resistance, the focus of the conflict is fundamentally different. The poem "Water" is rooted in collective historical trauma (slavery and colonialism) which is connected with elements of spirituality and nature (the ocean as a mass grave and a ritual site). This poem uses emotive, metaphorical diction, as well as personification and hyperbole. In contrast, the poem "Warning" focuses on a straightforward socio-political critique of the repression of the authorities in the present, using bold and everyday diction. The resistance in "Water" is spiritual and introspective, while in "Warning" it is a call for direct action ("fight!"). The conclusion of this study confirms that both poems are urgent poetic manifestations of the struggle for human dignity, demanding both historical reconciliation and political courage.